Lewy body-like alpha-synuclein inclusions trigger reactive microgliosis prior to nigral degeneration - Megan F. Duffy (5713772) (2018)
Background Converging evidence suggests a role for microglia-mediated neuroinflammation in Parkinson’s disease (PD). Animal models of PD can serve as a platform to investigate the role of neuroinflammation in degeneration in PD. However, due to features of the previously available PD models, interpretations of the role of neuroinflammation as a contributor to or a consequence of neurodegeneration have remained elusive. In the present study, we investigated the temporal relationship of neuroinflammation in a model of synucleinopathy following intrastriatal injection of pre-formed alpha-synuclein fibrils (α-syn PFFS). Methods Male Fischer 344 rats (N = 114) received unilateral intrastriatal injections of α-syn PFFs, PBS, or rat serum albumin with cohorts euthanized at monthly intervals up to 6 months. Quantification of dopamine neurons, total neurons, phosphorylated α-syn (pS129) aggregates, major histocompatibility complex-II (MHC-II) antigen-presenting microglia, and ionized calcium-binding adaptor molecule-1 (Iba-1) immunoreactive microglial soma size was performed in the substantia nigra. In addition, the cortex and striatum were also examined for the presence of pS129 aggregates and MHC-II antigen-presenting microglia to compare the temporal patterns of pSyn accumulation and reactive microgliosis. Results Intrastriatal injection of α-syn PFFs to rats resulted in widespread accumulation of phosphorylated α-syn inclusions in several areas that innervate the striatum followed by significant loss (~ 35%) of substantia nigra pars compacta dopamine neurons within 5–6 months. The peak magnitudes of α-syn inclusion formation, MHC-II expression, and reactive microglial morphology were all observed in the SN 2 months following injection and 3 months prior to nigral dopamine neuron loss. Surprisingly, MHC-II immunoreactivity in α-syn PFF injected rats was relatively limited during the later interval of degeneration. Moreover, we observed a significant correlation between substantia nigra pSyn inclusion load and number of microglia expressing MHC-II. In addition, we observed a similar relationship between α-syn inclusion load and number of microglia expressing MHC-II in cortical regions, but not in the striatum. Conclusions Our results demonstrate that increases in microglia displaying a reactive morphology and MHC-II expression occur in the substantia nigra in close association with peak numbers of pSyn inclusions, months prior to nigral dopamine neuron degeneration, and suggest that reactive microglia may contribute to vulnerability of SNc neurons to degeneration. The rat α-syn PFF model provides an opportunity to examine the innate immune response to accumulation of pathological α-syn in the context of normal levels of endogenous α-syn and provides insight into the earliest neuroinflammatory events in PD. Correction: Lewy body-like alpha-synuclein inclusions trigger reactive microgliosis prior to nigral degeneration: https://dx.doi.org/10.1186/s12974-018-1202-9, published online 25 May 2018. Other Information Published in: Journal of Neuroinflammation License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1186/s12974-018-1171-z